Triple bottom-line consideration of sustainable plant disease management: From economic, sociological and ecological perspectives - Dun-chun HE; Jeremy J. BURDON; Lian-hui XIE; Jiasui ZHAN (Journal of Integrative Agriculture, 2021)
Plant disease management plays an important role in achieving the sustainable development goals of the United Nations (UN) such as food security, human health, socio-economic improvement, resource conservation and ecological resilience. However, technologies available are often limited due to different interests between producers and society and lacks of proper understanding of economic thresholds and the complex interactions among ecology, productivity and profitability. A comprehensive synergy and conflict evaluation of economic, sociological and ecological effects with technologies, productions and evolutionary principles as main components should be used to guide sustainable disease management that aims to mitigate crop and economic losses in the short term while maintaining functional farm ecosystem in the long term. Consequently, there should be an increased emphasis on technology development, public education and information exchange among governments, researchers, producers and consumers to broaden the options for disease management in the future.